Seasonality of planktonic crustacean decapod larvae in the subtropical waters of Gran Canaria Island, NE Atlantic - Landeira, José M.; Lozano-Soldevilla, Fernando (Scientia Marina, 2018)
A monitoring programme was established to collect plankton samples and information of environmental variables over the shelf off the island of Gran Canaria during 2005 and 2006. It produced a detailed snapshot of the composition and seasonal assemblages of the decapod larvae community in this locality, in the subtropical waters of the Canary Islands (NE Atlantic), where information about crustacean phenology has been poorly studied. The larval community was mainly composed of benthic taxa, but the contribution of pelagic taxa was also significant. Infraorders Anomura (33.4%) and Caridea (32.8%) accounted for more than half the total collected larvae. High diversity, relatively low larval abundance throughout the year and weak seasonality characterized the annual cycle. However, in relation to the temporal dynamics of temperature, two distinct larval assemblages (cold and warm) were identified that correspond to periods of mixing and stratification of the water column. The results also indicate that larval release times and durations in the subtropical waters are earlier and longer than at other higher latitudes in the NE Atlantic. We detected the presence of larvae of six species that have not yet been reported from the Canary Islands (Pandalina brevirostris, Processa edulis, Necallianasa truncata, Parapenaeus longirostris, Crangon crangon, Nematopagurus longicornis). Finally, this study provides a baseline for future comparisons with respect to fishery pressure and climate variability in this subtropical region.